FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN HIPEREMESIS GRAVIDARUM PADA IBU HAMIL DI RB ZAKAT SURABAYA: FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN HIPEREMESIS GRAVIDARUM PADA IBU HAMIL DI RB ZAKAT SURABAYA - Abidah, Siska Nurul; Fauziyatun, Fauziyatun Nisa' (EMBRIO, 2019)
Nausea and vomiting are physiological things that occur in young pregnancies, but nausea and vomiting continue to get heavier which will cause hyperemesis gravidarum which can cause dehydration and acidooticosis. This study aims to analyze the factors associated with the incidence of hyperemesis gravidarum in pregnant women. This study uses a total sampling technique that is sampling done with a total population of 45 people for 3 months, the population and sample are pregnant women who check at RB Zakat Surabaya. Data collection in the form of a register at RB Zakat Surabaya in June-August 2019. Using Chi-square test. Statistical test results showed that there was a relationship between gravida and hyperemesis gravidarum (p = 0,000), there was a relationship between multiple pregnancy and hyperemesis gravidatum (p = 0.024), there was no relationship between hydatidiform mole and hyperemesis gravidarum (p = 0.222), no there is a relationship between gastritis and the occurrence of hyperemesis gravidarum (0.358). It is hoped that health workers will increase counseling and counseling for pregnant women to overcome complaints of hyperemesis gravidarum.